Diagnostic and Treatment Options to the Patients Presenting with Neurological Symptoms Caused by Celiac Disease - Jakubauskas, Domantas; Mameniškienė, Rūta (Neurologijos seminarai, 2024)
Celiac disease (CD) is a gastrointestinal disorder caused by the immune system’s response to gluten, involving both innate and adaptive immune reactions. It leads to various neurological issues, such as gluten ataxia, gluten neuropathy, epilepsy, and gluten encephalopathy. Although neurological presentations are rare in children, they are observed in up to 36% of adult patients with CD. Recent evidence suggests that these manifestations may be linked to gluten-related mechanisms, including antibody cross-reactions, immune-complex deposition, direct neurotoxicity, and, in severe cases, vitamin or nutrient deficiencies. However, there is still no consensus on whether serological, neurophysiological, or neuroimaging findings can effectively diagnose and monitor CD-associated neurological problems at an early stage. The identification of multimodal biomarkers and suitable neuroimaging tools could aid in the diagnosis, monitoring, and enhancement of the quality of life for individuals with neuroceliac disease. Nonetheless, it is essential to provide appropriate treatment to those with CD and neurological symptoms, as prolonged suffering may lead to irreversible disability. The primary treatment for neurological manifestations of gluten-related disorders is a strict gluten-free diet, although a small number of patients may require additional immunosuppressive therapy, typically using mycophenolate or intravenous immunoglobulins. In this literature review, our aim was to explore the relevant neurological disorders associated with CD, early diagnostic and treatment options to prevent related disability in affected patients. Clinicians should consider CD as a potential cause in individuals presenting with unexplained neurological dysfunction.
Keywords: Celiac disease; gluten ataxia; gluten neuropathy; epilepsy; gluten encephalopathy; diagnosis; treatment